(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Facial recognition plays an important role in surveillance systems, biology of medical applications, terrorist activities and identification of major disasters. The aim of this study is to provide gender-specific anthropometric facial measurements for three regions of Libya, contributing to the development of standard morphometric parameters for these populations. The results showed significant differences in all parameters studied between men and women. However, differences were observed between the parameters when analyzed by geographical origin. These results highlight the complexity of regional differences and the need for further research to validate gender-specific practices in specific populations.